Analisis Perbandingan Kinerja Keuangan Perbankan Listed di BEI Selama Pandemi dan Sesudah Pandemi Covid-19 Periode Tahun 2020-2024 - Rani, Anjar Kumala; Kiryanto, Kiryanto (Politeknik Negeri Ambon, 2025)
Introduction: This study uses CAR, NPL, LDR, BOPO, and ROA variables to analyze comparative financial performance. This study focuses on banking firms that were listed on the Indonesia Stock Exchange (IDX) during the period from 2020 to 2024.Methods: This research is a quantitative study with a comparative approach, processing data using SPSS 27.00 software and using the Wilcoxon Signed Rank test. Secondary data comes from documentation studies of the Indonesian Stock Exchange, companies’ annual financial reports, and other official sources.Results: Purposive sampling was used to select 26 banking companies as samples that met the research requirements. The research findings showed no significant differences in the CAR ratio between the pandemic and post-pandemic periods, reflecting the banking sector’s ability to maintain capital stability amid economic pressures. However, there were significant differences in the NPL, LDR, BOPO, and ROA ratios. During the pandemic, increases in NPLs and BOPO occurred due to decreased debtor repayment capacity and increased risk management costs, while decreases in LDR and ROA occurred due to weakened credit demand and increased operational costs and credit risk.Conclusion and suggestion: This research shows that the COVID-19 pandemic has significantly impacted banking financial performance. These findings are expected to serve as a reference for banking industry players, investors, and regulators in developing post-COVID-19 policy strategies. Keywords: CAR, NPL, LDR, BOPO, ROA, Financial Performance, Pandemic Covid-19